Pengembangan Media Puzzle Suku Kata Untuk Melatih Kemampuan Membaca Peserta Didik Kelas 1 SDN 05 Koto Baru - Apreasta, Lika; Anggrayn, Melisa; Rezeki, Sri (Jurnal Ilmiah Dikdaya, 2024)
This research aims to develop syllabic puzzle media to train students' reading skills in class 1 at SDN 05 Koto Baru. Thisresearch uses R&D (Research and Development) research. The development model used uses the ADDIE model which consists offive stages, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. The type of data taken isquantitative and qualitative data. The data development instruments that researchers used were validation sheets, practicalityquestionnaires and instrument effectiveness. The collection methods in this research are interview techniques, questionnairetechniques, and documentation. The data analysis techniques used are validity analysis, practicality analysis and effectivenessanalysis. Based on the product development and testing stages that have been carried out by researchers at SDN 05 Koto Baru onsyllable puzzle media to train class students' reading skills, validation of the development of syllable puzzle media shows that thesyllable puzzle media obtained an average percentage of 87.5 % with very valid categories, so the syllable puzzle media is said to besuitable for use. The practicality of syllabic puzzle media was assessed from the questionnaire responses from educators andresponses to the development of syllabic puzzle media by obtaining a percentage from educators of 92% and 80% which both fall intothe very practical category, so the average value is 86% . The effectiveness of syllabic puzzle media is assessed from the results of thequestionnaire interest score with an average percentage of 82% in the very effective category. So it is very effective to use syllabicpuzzle media to improve learning outcomes, interest and motivation to learn.